2022
DOI: 10.3389/fmed.2021.783626
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Use of Post-exposure Prophylaxis for HIV Prevention Among Men Who Have Sex With Men: A Systematic Review and Meta-Analysis

Abstract: Background: The use of post-exposure prophylaxis (PEP) is effective in reducing HIV risk, but it is underused by men who have sex with men (MSM) due to certain psychological and sociostructural factors. This article assessed the awareness and use of PEP among MSM in an effort to increase the visibility and uptake of PEP among at-risk populations.Methods: We conducted a systematic literature search of the PubMed, Web of Science, PsycINFO, and Google Scholar electronic databases. Studies were screened for inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Some authors have found, in the United States, a lower or similar rate of knowledge on prevention among MSM than described in the present study (16,24) . A recent meta-analysis involving 12,579 MSM found that the combined estimate of the proportions of MSM who were aware of PEP was 59.9%, reinforcing the maintenance of a low-level knowledge about the strategy (25) . The engagement and education strategies undertaken by governmental and non-governmental organizations targeting the MSM population may impact the diffusion of this knowledge.…”
Section: Discussionmentioning
confidence: 95%
“…Some authors have found, in the United States, a lower or similar rate of knowledge on prevention among MSM than described in the present study (16,24) . A recent meta-analysis involving 12,579 MSM found that the combined estimate of the proportions of MSM who were aware of PEP was 59.9%, reinforcing the maintenance of a low-level knowledge about the strategy (25) . The engagement and education strategies undertaken by governmental and non-governmental organizations targeting the MSM population may impact the diffusion of this knowledge.…”
Section: Discussionmentioning
confidence: 95%
“…HIVST research and new product development are ongoing. Research suggests that the pace of endorsing and adopting a new biomedical innovation as a mainstream strategy can be slow ( 76 78 ), taking more than a decade for new products to be integrated into routine clinical practice ( 79 ). We have witnessed the slow and inconsistent uptake of other new HIV and STI prevention technologies, as reflected in experience with daily oral pre-exposure prophylaxis and likely with the cabotegravir 2-month injectable and the dapivirine vaginal ring.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2022 systematic review of over 12 000 MSM, the pooled estimate of individuals who were aware of PEP was modest, at 59.9% (95% confidence interval [CI]: 50.5–68.7), and that of those who had previously used PEP was very low, at 4.9% (95% CI: 2.4–9.8). 18 The study concludes that PEP is an underused HIV prevention strategy among MSM and that once individuals become aware of PEP, the majority are willing to use it if they are supported appropriately in terms of individual, social, and structural barriers. We know this ‘under use’ is also true among young women, both for unanticipated sexual exposure and sexual violence.…”
Section: Introductionmentioning
confidence: 94%